Surgical Management of Giant Genital Condyloma Acuminata by Using Double Keystone Flaps - Peri Eriad Yunir; Chaidir A. Mochtar; Agus Rizal A. H. Hamid; Chaula L. Sukasah; Rainy Umbas (Case Reports in Urology)
Condyloma acuminata in the external genitalia (genital warts) is a sexually transmitted disease that is often caused by human papillomavirus (HPV). We report a case of giant genital condyloma acuminata in a 35-year-old male patient with HIV comorbidity treated by wide surgical excision. Excision defect was covered with split thickness skin graft (STSG) and double keystone flaps. There was no complication after surgery. Ten months following surgery, there was no new condyloma lesion and the patient had normal voiding and erectile functions.